The Role of Banking Finance and Monetary Policy in Enhancing Human Development Index in Sudan (1999-2018) - Mustafa, Omer Allagabo Omer (International Journal of Economics and Financial Issues, 2020)
Through a regression model, the study highlighted the role of the banking finance and monetary policy in enhancing human development index (HDI) in Sudan during the period (1999-2018). The descriptive analytical approach was used to achieve the objectives of the study. Secondary data were collected from; annual reports of the Central Bank of Sudan, World Bank and UNDP database. Inflation rates were used to indicates the efficiency of monetary policy. To ensure stationary of the variables used to estimate the model, Augmented Dickey-Fuller (ADF) and unit root tests were calculated. Results of ADF test show that, the set of variables are stationary at 1st difference. Ordinary least squares method was used to determine and conclude the direction of relations between the HDI and variables. The results found that there is a positive relationship between HDI and changes in provision of banking finance and inflation during the period of the study. Moreover, it’s found that, monetary policy in term if inflation indirectly contributed to enhances HDI through money supply increase. The study recommends the commercial banks in Sudan to expand granting finance to the various economics activities especially the production sector. Furthermore, monetary authority should adopt contractionary monetary policy to reduce inflation and improve the standard of living. Keywords: Banking Finance, Monetary policy, Inflation, Human Development Index JEL Classifications: E3, G21, I31, O5 DOI: https://doi.org/10.32479/ijefi.9902